2018
DOI: 10.3892/ol.2018.9870
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory biomarkers in prognostic analysis for patients with glioma and the establishment of a nomogram

Abstract: Being biomarkers that reflect host nutritional and immune status, prognostic nutritional index (PNI) and neutrophil/lymphocyte ratio (NLR) have been identified to be independent prognostic factors in various malignancies. The aim of the present study was to determine the predictive value of these parameters for the prognosis of patients with glioma. Hematological and clinicopathological data were retrospectively analyzed from 128 patients with glioma who underwent brain tumor resection between January 2008 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…1. A total of 16 articles published between 2013 and 2019 were incorporated in our study [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The data of 2275 patients in whom the prognostic significance of NLR was assessed were included.…”
Section: Description Of the Trialsmentioning
confidence: 99%
“…1. A total of 16 articles published between 2013 and 2019 were incorporated in our study [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The data of 2275 patients in whom the prognostic significance of NLR was assessed were included.…”
Section: Description Of the Trialsmentioning
confidence: 99%
“…Unfortunately, there were still occasional studies to indicate PNI was not associated with prognosis. [ 13 , 14 , 20 ] Hereby, their prognostic significance also needs further assessment. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that PLR was not an independent predictive index of LGGs, which was consistent with some previous reports in gliomas. 45 , 46 A recent meta-analysis of 18 studies containing 3261 patients showed that NLR [hazard ratio (HR): 1.38; 95% CI: 1.09–1.74; p = 0.008] was one of the independent indices for predicting the OS of gliomas. 45 In the present study, elevated NLR was statistically significant in univariate analysis but not multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%